2020
DOI: 10.1001/jamasurg.2020.2423
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Primary Hyperparathyroidism Screening Among US Veterans With Kidney Stones

Abstract: IMPORTANCE Approximately 3% to 5% of patients with kidney stones have primary hyperparathyroidism (PHPT), a treatable cause of recurrent stones. However, the rate of screening for PHPT in patients with kidney stones remains unknown.OBJECTIVES To estimate the prevalence of parathyroid hormone (PTH) testing in veterans with kidney stones and hypercalcemia and to identify the demographic, geographic, and clinical characteristics of veterans who were more or less likely to receive PTH testing. DESIGN, SETTING, AND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 35 publications
1
34
1
1
Order By: Relevance
“…This study assessed the clinical value of undertaking blood tests to screen for metabolic disorders in patients presenting with kidney stones. Primary hyperparathyroidism has been reported in 0.5-5% of the stone-forming population [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study assessed the clinical value of undertaking blood tests to screen for metabolic disorders in patients presenting with kidney stones. Primary hyperparathyroidism has been reported in 0.5-5% of the stone-forming population [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, the National Institute of Health and Care Excellence (NICE) recommends that adults presenting with ureteric or renal stones undergo metabolic screening with a serum calcium blood test alone [6]; an elevated serum calcium level may indicate previously unrecognized hyperparathyroidism, granulomatous disease or malignancy [5]. The NICE committee was unable to identify any evidence to inform recommendations for metabolic blood tests in patients with kidney stones, but made note of the high prevalence of primary hyperparathyroidism in these individuals and the low cost of serum calcium testing [6,[8][9][10]. In addition to serum calcium, the European Association of Urology (EAU) recommends that serum urate is checked routinely in emergency urolithiasis patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a simple means with which to diagnose primary hyperparathyroidism, for various reasons, this is a diagnosis that is often overlooked by lack of and/or incorrect interpretation of biochemical testing. [12][13][14][15][16][17] Multiple studies have shown that only approximately 30% of patients with documented hypercalcemia have ever had a PTH level assessed. [12][13][14][15][16][17] However, the frequency range at different facilities described in a single study varied widely from as low as 4% to as high as 57%.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Multiple studies have shown that only approximately 30% of patients with documented hypercalcemia have ever had a PTH level assessed. [12][13][14][15][16][17] However, the frequency range at different facilities described in a single study varied widely from as low as 4% to as high as 57%. 16 Hypercalcemia of malignancy (HCM) is an important complication of malignancy, most often seen in advanced stages of the clinical course of a patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation